PARTISIPASI MASYARAKAT DALAM PELAKSANAAN INSTRUKSI BUPATI NOMOR 01 TAHUN 2012 TENTANG PROGRAM PENGUATAN INFRASTRUKTUR PEDESAAN, DI DESA PENAMPI, KECAMATAN BENGKALIS PADA TAHUN 2012-2013 - Firdaus " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study was conducted to determine’s the community’sparticipation implementation of the regent instruction number 01 of 2012 on strenghthening on ruralinfrastructure in 2012-2013 in the Penampi village,Bengkalis regency were reviewed based on indicators of successful implementation of INBUP-PPIP.The main problem in this study is the decreasing number of communities participation that ocured in 2013,meanwhile the activities in increase basic infrastructure,.The theory in this research is the policy theory (teori kebijakan) and the theory of community participation in development (teori partisipasi masyarakat dalam pembangunan).this reseach uses descriptive method by using aproach of kualitatif.this research uses purposive sampling and snowball sampling, namely interview with speakers as an object of information that purpose to achieved the goal. this research used primary data and secondary data has obtained throught observation and interview with informants.Based on the result of the analysis of the research data in order to uncover and answer reseacrh question related to the analysis of public participation in the implementation of INBUP-PPIP program has been see from the stage of planning, implementation, and maintenance associated with indicators of the success of the program that focuses on the self-help and mutual help villagers of penampi, it’s conclude that the villagers was participated in the form of attendance at meetings and village meeting, willingness to take a part of the OMS, the contribution of labor and land. however, there has been no participation in maintance. While the declaine that occurred in 2013 the impactof the probelms that occurred in the 2012 and as well as in the public incomprehension towards INBUP-PPIP program it self that gave birth to reluctance to participate even have an impact on mutual assistance society of Penampi villagesIn addition,there are also constrain faced by the community participation in the implementation of INBUP-PPIP program in the village of Penampi,the time of the public,professionalism companion villages in the initial period 2012-2013 the implementation of that program, Pendamping Desa Penampi do not reside in that villageKeyword : community participation, INBUP-PPIP, Desa Penampi